Gigabit networking - Partridge, Craig ([S.l.] : Addison-Wesley Professional, 1994)
We are fast entering the age of gigabit networking, where information ispassed along wide area and local area networks at speeds surpassing onebillion bits per second. With improvements in fiber optic signalling and thedevelopment of inexpensive high-performance computers, both thecapability and the demand for gigabit networking are here. * As a networking professional who needs to prepare for the immediatefuture of computer networking, you will find Gigabit Networking afascinating and practical look at the advances that are making high-speednetworking a reality. Key technologies, important protocols, applications,and the practical issues involved in implementing gigabit networks are alladdressed. The book covers in detail such topics as: **- Fiber optics (written for non-engineers) *- Cell and non-cell networking, including Asynchronous Transfer Mode (ATM) *- Exciting applications that utilize gigabit networking *- Integrating gigabit networking into existing systems *- Adapting today's protocols for gigabit networking In addition to the current status of the technology, Gigabit Networking looks ahead to the ongoing research that will shape the future of gigabit networking. This important book will bring you up to date on the state of gigabitnetworking, and will give you the knowledge you need to launch yourselfinto the age of truly high-speed networking.